Peran Kelompok Tani Untuk Meningkatkan Kesejahteraan Petani di Desa Mekarwangi Kecamatan Lembang Kabupaten Bandung Barat - yukeu sumiati; Dewi Rahmi (UNISBA Press, 2023)
Abstract. Farmer groups are formed to facilitate the acquisition of agricultural inputs such as fertilizers, seeds and medicines, and the price of agricultural products can be decided together with the farmer group. Gapoktan was formed to address common agricultural problems and to strengthen farmers' bargaining power in the input market and domestic products in response to government programs that require farmer groups. After the government program is over, farmers stop joining farmer groups. The purpose of the study was to determine the role of farmer groups to improve the welfare of farmers in Mekarwangi village. The research method is descriptive combined with quantitative methods using basic data obtained by distributing questionnaires to respondents from 30 farmer groups. Analysis used quantitative methods by evaluating the results of respondents' questionnaires with a Likert scale. Based on research on 30 respondents, the gapoktan plays an important role for welfare with indicators of increased income, family education, health, housing and transportation improvements. Keywords: The role of farmer group, Farmer welfare, Horticulture. Abstrak. Kelompok tani dibentuk untuk memfasilitasi perolehan input pertanian seperti pupuk, bibit dan obat-obatan, selain itu harga hasil pertanian dapat diputuskan bersama dengan kelompok tani. Gapoktan dibentuk untuk mengatasi masalah umum pertanian dan untuk memperkuat daya tawar petani di pasar input dan produk dalam negeri menanggapi program pemerintah yang membutuhkan kelompok tani. Sesudah program pemerintah selesai, petani berhenti bergabung dengan gapoktan. Tujuan penelitian yaitu untuk mengetahui peran kelompok tani untuk meningkatkan kesejahteraan petani di desa Mekarwangi. Metode penelitian yaitu deskriptif dipadukan dengan metode kuantitatif menggunakan data dasar yang diperoleh dengan menyebarkan kuesioner kepada responden dari 30 kelompok petani. Analisis digunakan metode kuantitatif dengan mengevaluasi hasil kuesioner responden dengan skala Likert. Berdasarkan penelitian terhadap 30 responden, menyatakan gapoktan berperan penting untuk kesejahteraan dengan indikator peningkatan pendapatan, pendidikan keluarga, kesehatan, perbaikan tempat tinggal dan transportasi. Kata Kunci: Peran kelompok tani, Kesejahteraan petani, Hortikultura.